2016
DOI: 10.1149/2.0201605jes
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Polysulfides during Charge/Discharge of the Room-Temperature Na/S Battery Using TEGDME Electrolyte

Abstract: The charge-discharge process of the room-temperature Na/S battery is studied using the Na/S cell with tetraethylene glycol dimethyl ether (TEGDME) and the solid electrolyte. The solid electrolyte is a barrier for chemical mass transport between the anode and the cathode. The sodium polysulfides as reaction products in TEGDME could therefore be investigated without interference from the anode side. During discharge, the color of the TEGDME electrolyte changes from transparent to brown, yellowish-green, and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 19 publications
4
75
0
Order By: Relevance
“…The composition close to solid state Li 2 S, is insoluble in electrolyte, but intermediate polysulfides or so‐called high‐order polysulfides (Li 2 S x , 4 ≤ x ≤ 8) can be dissolved in organic electrolytes, causing consistent capacity fading due to the continuous loss of active materials. Similarly, the electrochemical properties would be affected by the sodium polysulfides formed from the mixed Sn–S nanocomposites after the conversion reaction . Additionally, the volume expansion of the metallic Sn formed after the subsequent alloying reaction can be the reason for the severe capacity fade, accompanying the degradation of active material and the pulverization for a discharge/charge process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition close to solid state Li 2 S, is insoluble in electrolyte, but intermediate polysulfides or so‐called high‐order polysulfides (Li 2 S x , 4 ≤ x ≤ 8) can be dissolved in organic electrolytes, causing consistent capacity fading due to the continuous loss of active materials. Similarly, the electrochemical properties would be affected by the sodium polysulfides formed from the mixed Sn–S nanocomposites after the conversion reaction . Additionally, the volume expansion of the metallic Sn formed after the subsequent alloying reaction can be the reason for the severe capacity fade, accompanying the degradation of active material and the pulverization for a discharge/charge process.…”
Section: Resultsmentioning
confidence: 99%
“…Although the oxidation state of the sulfur present in the electrode materials depends on the bonding strength with Sn, the multiple doublets S2p 3/2 ‐S2p 1/2 located in 162.3 and 163.7 eV, respectively, have a binding energy difference of 1.4 eV, facilitating the understanding of the trends in the S2p spectra in the discharge/charge process. The sulfur of the electrode material is converted to sodium polysulfide (Na 2 S x ; 2 ≤ x ≤ 8) during the conversion reaction, ultimately becoming sodium disulfide (Na 2 S) . The binding energy of sulfur ions depends on their chemical state in the sodium polysulfide chain.…”
Section: Resultsmentioning
confidence: 99%
“…In ether‐based organic electrolytes, the conventional shuttle effect occurs with dissolved NaPSs shuttling from the cathode to the anode area and form a concentration gradient. They then react with the sodium anode to form low‐order NaPSs and even insoluble Na 2 S 2 /Na 2 S, which accumulates on the surface, leading to rapid loss of active material and deterioration of the Na anode . It should be pointedout that the dissolution of NaPSs is far worse than that of lithium polysulfides (LiPSs) in ether‐based electrolyte, where it was reported that the traditional tetraethylene glycol dimethyl ether (TEGDME) electrolyte can dissolve 10.56 m Na 2 S 8 13a.…”
Section: Introductionmentioning
confidence: 99%
“…They then react with the sodium anode to form low‐order NaPSs and even insoluble Na 2 S 2 /Na 2 S, which accumulates on the surface, leading to rapid loss of active material and deterioration of the Na anode . It should be pointedout that the dissolution of NaPSs is far worse than that of lithium polysulfides (LiPSs) in ether‐based electrolyte, where it was reported that the traditional tetraethylene glycol dimethyl ether (TEGDME) electrolyte can dissolve 10.56 m Na 2 S 8 13a. In contrast, the NaPSs would rapidly react with carbonate‐based electrolyte solvents, such as ethylene carbonate (EC), leading to the direct loss of active S species through substitution or nucleophilic addition reactions .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14] Thus, the electrochemical performance of Li S batteries has been notably improved in terms of cyclability and capacity. [15][16][17][18][19][20][21] This feature is thought to be associated with the solubility and solvated structure of polysulfide intermediates, which are sensitive to the surrounding solvent system. [10][11][12][13][14] The tendency of many studies being oriented on physical methods may be attributed to the lack of an in-depth understanding of the physicochemical properties of polysulfides in an electrolyte, such as their chemical or physical interactions with electrolytes and the importance of their solubility on the electrochemical behavior of a sulfur cathode.…”
Section: Introductionmentioning
confidence: 99%